Assessment Of In-Vitro Bioequivalence Parameters Of Some Brands Of Paracetamol Tablets Produced In South West Nigeria - A. Adeleye, Olutayo; O. Ayorinde, John; N. Femi-Oyewo, Mbang (The Nigerian Journal of Pharmacy, 2019)
Background: Solid dosage forms, especially tablets are the commonest product lines in pharmaceutical industries. This study was therefore conducted to assess the in-vitro bioequivalence of five brands of paracetamol (500mg) tablets manufactured in South West Nigeria to ascertain its quality. Methods: The parameters assessed were, physical properties (tablet dimensions, shape, colour, and weight variation), mechanical properties and assay (hardness, friability, and content uniformity), and release properties (disintegration, dissolution, release kinetics and mechanism). Results: All the paracetamol brands complied with pharmacopoeia specifications for percentage weight variation and drug content uniformity while two brands A and D failed the hardness test and one brand, E failed the friability test. The disintegration times for the entire brand were within limit. Brand A had the shortest disintegration time and t25%, followed by brand C. They all released at more than 80% paracetamol within 30 mins as specified by the USP in the following order A<C< D< B< E. Conclusion: The results of most of the biopharmaceutical parameters assessed complied well with pharmacopoeia specification. So, we can conclude that the paracetamol (500mg) tablets produced in South West, Nigeria used in this study were found to be of good quality and acceptable bioequivalent properties.